Concomitant induction of SLIT3 and microRNA-218–2 in macrophages by toll-like receptor 4 activation limits osteoclast commitment - Eun-Young Kim; Ji-Eun Kim; Soo-Hyun Chung; Ji-Eun Park; Dohee Yoon; Hyo-Jin Min; Yoolim Sung; Soo Been Lee; Seong Who Kim; Eun-Ju Chang (Cell Communication and Signaling, 2023)
Abstract Background Toll-like receptor 4 (TLR4) conducts a highly regulated inflammatory process by limiting the extent of inflammation to avoid toxicity and tissue damage, even in bone tissues. Thus, it is plausible that strategies for the maintenance of normal bone-immunity to prevent undesirable bone damage by TLR4 activation can exist, but direct evidence is still lacking. Methods Osteoclast precursors (OCPs) obtained from WT or Slit3-deficient mice were differentiated into osteoclast (OC) with macrophage colony-stimulating factor (M-CSF), RANK ligand (RANKL) and lipopolysaccharide (LPS) by determining the number of TRAP-positive multinuclear cells (TRAP+ MNCs). To determine the alteration of OCPs population, fluorescence-activated cell sorting (FACS) was conducted in bone marrow cells in mice after LPS injection. The severity of bone loss in LPS injected WT or Slit3-deficient mice was evaluated by micro-CT analysis. Result We demonstrate that TLR4 activation by LPS inhibits OC commitment by inducing the concomitant expression of miR-218–2-3p and its host gene, Slit3, in mouse OCPs. TLR4 activation by LPS induced SLIT3 and its receptor ROBO1 in BMMs, and this SLIT3-ROBO1 axis hinders RANKL-induced OC differentiation by switching the protein levels of C/EBP-β isoforms. A deficiency of SLIT3 resulted in increased RANKL-induced OC differentiation, and the elevated expression of OC marker genes including Pu.1, Nfatc1, and Ctsk. Notably, Slit3-deficient mice showed expanded OCP populations in the bone marrow. We also found that miR-218–2 was concomitantly induced with SLIT3 expression after LPS treatment, and that this miRNA directly suppressed Tnfrsf11a (RANK) expression at both gene and protein levels, linking it to a decrease in OC differentiation. An endogenous miR-218–2 block rescued the expression of RANK and subsequent OC formation in LPS-stimulated OCPs. Aligned with these results, SLIT3-deficient mice displayed increased OC formation and reduced bone density after LPS challenge. Conclusion Our findings suggest that the TLR4-dependent concomitant induction of Slit3 and miR-218–2 targets RANK in OCPs to restrain OC commitment, thereby avoiding an uncoordinated loss of bone through inflammatory processes. These observations provide a mechanistic explanation for the role of TLR4 in controlling the commitment phase of OC differentiation. Video Abstract